Answer:
![(fog)(12)=-6](https://tex.z-dn.net/?f=%28fog%29%2812%29%3D-6)
Step-by-step explanation:
Recall that the notation:
is the same as:
which means the value of the function f when you give it as input the value obtained by evaluating g(12).
Therefore, we need to start finding what g(12) is using the definition :
and evaluating it as x = 12.
![g(x)=\sqrt{x-8}\\g(12)=\sqrt{12-8}\\g(12)=\sqrt{4}\\g(12)=2](https://tex.z-dn.net/?f=g%28x%29%3D%5Csqrt%7Bx-8%7D%5C%5Cg%2812%29%3D%5Csqrt%7B12-8%7D%5C%5Cg%2812%29%3D%5Csqrt%7B4%7D%5C%5Cg%2812%29%3D2)
So now we use this answer "2" as input for f(x):
![f(x)=-4x+2\\f(2)=-4(2)+2\\f(2)=-8+2\\f(2)=-6](https://tex.z-dn.net/?f=f%28x%29%3D-4x%2B2%5C%5Cf%282%29%3D-4%282%29%2B2%5C%5Cf%282%29%3D-8%2B2%5C%5Cf%282%29%3D-6)
Therefore, ![(fog)(12)=-6](https://tex.z-dn.net/?f=%28fog%29%2812%29%3D-6)
Answer:
she never brought her cost up when they got another cup cake it should
x y
1 3.50
2 7
3 10.50
4 14
i ant really graph them
Step-by-step explanation:
C, E, and F have 50 50 chance